WONDERS LOST AND FOUND a celebration of the archaeological work of. (ARCHAEOPRESS, 2020)
Twenty-one contributions, written by friends and colleagues, reflect the wide interests of Professor Michael Vickers; from the Aegean Bronze Age to the use made of archaeology by dictators in the modern age. Seven contributions relate to Georgia, where the Professor has worked most recently, and made his home.